Berkah Finansial: Tantangan dan Implementasi Perencanaan Keuangan Syariah Generasi Z Kota Langsa - Mirza, Rinda; Hisan, Khairatun; Maulana, Zefri (Fakultas Ekonomi dan Bisnis Islam, 2024)
This study aims to identify the challenges faced by Generation Z in Langsa City in adopting sharia financial planning. Although sharia financial planning offers many benefits, many of them have difficulty understanding and implementing sharia financial principles effectively. This study uses a field research method with a descriptive qualitative approach, involving five informants from Generation Z selected through the Snowball Sampling technique. Primary data were obtained through direct interviews, while secondary data came from literature studies. Key findings indicate variations in the understanding and implementation of sharia financial planning, where some informants have implemented planning systematically, while others are more spontaneous and less organized. The main obstacles faced include a lack of in-depth understanding of sharia principles, as well as the influence of a consumptive lifestyle that hinders the implementation of sharia principles such as the prohibition of usury, gharar, and maysir. This study emphasizes the importance of sharia financial education and literacy to improve financial management in accordance with sharia principles among Generation Z.